Indonesia’s Industrial Diplomacy: Prospects and Challenges - Putri, S O; Ginanjar, G (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This paper aims to identify the prospects and challenges from Indonesia's industrial diplomacy. Indonesian industry contributes almost 20 percent to Gross Domestic Product (GDP). Industrial sector is the backbone of the Indonesian economy, besides having a high value (export) also provide jobs. Recent trend Indonesia’s national industries growing at a low speed, especially during the covid-19 pandemic. In the midst of this uncertain situation, the national industry is still show a good performance. Industrial diplomacy is urgently needed. The research method was a qualitative approach, which data collection technique was conducted through literature review. The result of this paper shows that Indonesian government continues to strive to improve the competitiveness of the national industry so that it can be competitive at the global level through industrial diplomacy. Some challenges like trade barriers, product strategy, synergy and coordination, and the low number of representations of industrial diplomats became challenges in industrial diplomacy. With the right strategy and successful implementation of Making Indonesia 4.0, Indonesia has an opportunity to become the top 10 largest economies in the world by 2030.